METODE ASSESSMENT DESKRIPTIF KUALITAS VISUAL LANSKAP KAMPUS DI INDONESIA, Kasus Studi: Lanskap Kampus ITB - F Firmansyah (TATALOKA, 2011)
Campus landscape is designed in order to proposed the institution philosophy, build the campus character and sense of place. A Purpose of this research is developing visual quality assessment method of campus landscape in Indonesia and mapping a common and special characteristic of landscape visual quality in case study. The first stage of this research is finding all of indicators, variables, and criteria of campus landscape visual quality in Indonesia. The data is collected by physical inventory. Physical inventory is collecting all of physical data to get campus landscape significance. The next stage of this research is to make an assessment of landscape visual quality by descriptive assessment method, to know and describe the qualitative dimension of landscape quality, The last stage is making the landscape quality mapping area and common or specific factors that influence them